Electronic Money As A Contemporary Financial Product From The Perspective of Islamic Economic Law (Juridical, Philosophical, And Sociological Studies) - Muhammad Syarif Hidayatullah (Faculty of Sharia and Law Universitas Islam Nahdlatul Ulama, 2023)
Electronic money is a means of payment in contemporary financial transactions. This paper aims to analyze the existence of electronic money as a financial product that is part of contemporary economic activity through juridical, philosophical, and sociological studies. In juridical studies, through the study of fiqh muamalah, DSN-MUI has formulated a fatwa on sharia electronic money as an answer to the presence of electronic money in modern economic activities. The fatwa lists the mashadir al-ahkam and Islamic legal maxim related to views on the legality of electronic money. It formulates views on the agreements that apply to electronic money. In philosophical studies through the study of maqashid sharia, the existence of electronic money is related to hifzh al-mâlin terms of security and safeguarding assets in transactions, and during the pandemic in the previous year, hifzh an-nafs also applied, and there are benefits in the framework of maslahah, including the category of maslahah mursalah in the use of electronic money. In addition, in sociological studies through the study of socioeconomic behavior, there was a shift from conventional/ manual payment methods to digital because of the benefits and advantages offered; thus, a cashless culture occurred.Electronic money is a means of payment in contemporary financial transactions. This paper aims to analyze the existence of electronic money as a financial product that is part of contemporary economic activity through juridical, philosophical, and sociological studies. In juridical studies, through the study of fiqh muamalah, DSN-MUI has formulated a fatwa on sharia electronic money as an answer to the presence of electronic money in modern economic activities. The fatwa lists the mashadir al-ahkam and Islamic legal maxim related to views on the legality of electronic money. It formulates views on the agreements that apply to electronic money. In philosophical studies through the study of maqashid sharia, the existence of electronic money is related to hifzh al-mâlin terms of security and safeguarding assets in transactions, and during the pandemic in the previous year, hifzh an-nafs also applied, and there are benefits in the framework of maslahah, including the category of maslahah mursalah in the use of electronic money. In addition, in sociological studies through the study of socioeconomic behavior, there was a shift from conventional/ manual payment methods to digital because of the benefits and advantages offered; thus, a cashless culture occurred